The influence of removing home advantage on the Chinese Football Super League - Bo Han; Lang Yang; Pengyu Pan; Antonio García-; Can Yang; Tianbiao Liu (BMC, 2022)
Abstract Background Due to the COVID-19 pandemic, the 2020 season Chinese Super League (CSL) was held in neutral venues, this study aims to analyse the impact of removing home advantage (HA) in CSL. Method 240 games of the CSL 2019 season (home and away double round-robin system) and 160 games of the 2020 season (in neutral venues) were analysed. 27 technical and tactical performance indicators were involved as dependent variables. A multiple linear regression model was established to analyse the influence of removing HA on the performance indicators. Results After moving from home stadium to neutral venue in 2020 season, goal, shot, shot on target, shot from outside box, shot from inside box, shot on target from inside box, corner kick, key pass, cross, breakthrough, tackle decreased significantly (p < 0.05), while yellow card and foul increased steeply (p < 0.05). Comparing with playing away match, in neutral venue, free kicks and pass accuracy enhanced radically (p < 0.05), while tackle, clearance and block shot dropped noticeably (p < 0.05). Conclusion When removing HA and playing in the neutral venue, teams' performance dropped significantly. This study confirmed the positive impact of HA on the teams' performance and may help elite football teams make proper playing strategies regarding different match locations.